Association between obesity indicators and retinopathy in US adults: NHANES 2005–2008 - Wang, Chuan-Xi; Kuang, Miao; Hou, Jing-Jing; Lin, Si-Yu; Liu, Sheng-Zhen; Bao, Ning; Jiang, Zheng-Xuan (Frontiers in Nutrition, 2025)
BackgroundObesity is harmful to the retina. Few studies have examined obesity indicators for retinopathy, and our research is intended to elucidate this relationship.MethodsThis study assessed the association between obesity indicators and retinopathy using weighted multifactorial logistic regression, participants from the National Health and Nutrition Examination Survey (NHANES). The stability of the relationship was tested by subgroup analysis. Moreover, restricted cubic spline (RCS) was used to test for a non-linear relationship between them. Finally, Receiver Operating Characteristic (ROC) curves were applied to compare the prognostic value of each obesity indicator for retinopathy.ResultsAfter adjusting the confounding factor, weighted logistic regression showed positive associations between body roundness index (BRI), conicity index (CI), waist-to-height ratio (WHtR), tri-ponderal mass index (TMI), weight-adjusted-waist index (WWI), body mass index (BMI), and retinopathy. RCS curves found linear correlations between BRI, CI, WHtR, TMI, and WWI with retinopathy, except for BMI. Subgroup analyses showed no significant interactions between age, sex, ethnicity, and education subgroups. ROC curves showed that WWI had the highest predictive value for retinopathy.ConclusionOverall, increased levels of these obesity indicators increase the likelihood of developing retinopathy.